SOCIETY. (Beijing Review, 2017)
The article offers China news brief as of May 2017. Cyberspace authority of China has issued warning to computer users to install and upgrade computer security software to avoid ransomware attacks, findings of the survey which found that 7 percent of university students has experienced harassment fom unidentified people on their college campuses and expansion of reform in public hospitals in China such as medical system, hospital management and medical insurance.